“A Neo-Historical Study of “Dara Shukoh” by Qazi Abdul Sattar” - Rukhsana Yasmeen; Dr. Aqlima Naz (Al-Qanṭara, 2024)
This article deals with the Novel Dara Shukoh by Qazi Abdul Sattar.It is based on techniques of study of Neo-Historicism. This article centers on exploring different angles of the personality of Mughal Prince Dara Shukoh. With the symbolic study of the life of Dara Shukoh, we can sort guidance in current socio-economic scenario. Neo-historicism believes in the relationship between literature and history. That is, literature is subject to civilization in its creative oppression. No literary art is outside the scope of civilization and culture. When the writer creates literature in a genre, he is actually expanding his ideas by staying within the limits of that cultural heritage. According to the neo-historicists, literature is the result of the demands of a particular time and place. Therefore, they do not consider literature as independent. New Criticism and Reconstruction showed negativity about the importance of background in literature. And they consider the literature to be composed in its foreground. According to New Criticism, literature is self-sufficient and artwork interprets itself, but neo-historicism disagreed with this assumption. According to neo-historicism, art cannot be autonomous, independent and self-sufficient. Apart from history and the past, the shadows of civilization and culture go hand in hand in the creation of literature.